KONSEP MUTU DAN TOTAL QUALITY MANAJEMENT (TQM) DALAM DUNIA PENDIDIKAN - Asmuni Asmuni (Ta'dib: Jurnal Pendidikan Islam, 2013)
Recently, educational world is so striking because the government has been been doing and focusing on some efforts to build the concept of educational quality. One of the steps is a curriculum renewal in 2013. Although the 2013 curriculum has similar substance as the previous curriculum, one difference only lies on the method, namely Thematic Method. However, the curricullum cannot be separated from the quality of education itself that needs to be considered carefully, and great confidence arises when a new policy with extraordinary vision to 2025 that is to establish “smart and competitive Indonesian pupil (Perfect/ generous human being)". Although, like it or not if we analyze together that education in Indonesia, especially regarding to the quality, it can be said that it is much weaker compared to other countries in Southeast Asia such as Malaysia, Singapore, and Thailand. Therefore, the solution is to improve the quality of culture, and it is supposed to be a priority for the nation's education today.Of course, the whole matter cannot be separated from the Total Quality Management (TQM), which is the chief of the concept of quality. Eventhough at the beginning TQM  itself was used by the company or business sector but today has grown up and spread to the world of education. It is because basically, the management system between the company and the management of the education system is relatively the same, especially related to the primary goal of TQM that is to give priority to customer satisfaction and quality compared to other things. Thus, the quality of education is a key sector for TQM concepts to develop an institution variously, creatively and innovatively.